Evaluating practices toward dental health among primary school children in Rwanda - Janviere Mukabizimana; Dieudonne Kayiranga; Godfrey Katende; Jean Bosco Munyemana (BMC, 2024)
Abstract Background Dental diseases pose a global health problem that significantly affects overall well-being and quality of life. They are frequently neglected in many regions, despite the availability of preventive measures and it remains unclear whether these measures are effectively implemented in practice. Therefore, this study aimed to evaluate dental health practices among primary school children in both rural and urban areas of Rwanda. Methods A cross-sectional study was conducted on 195 school children including 96 from a rural area and 99 from an urban area. Data were collected through a questionnaire and analyzed using SPSS version 21. To compare practices between the rural and urban groups, Fisher's exact test was utilized, with a significance level set at 0.05. Results The findings show significant differences in dental health practices between rural and urban areas, revealing that rural children were less likely to visit the dentist regularly (p = 0.026) and had a higher frequency of sugary drink consumption (p = 0.002). Additionally, disparities were found in the materials used for tooth brushing (p < 0.001) and the timing of toothbrush replacement (p = 0.011), indicating that rural children often use inappropriate brushing materials and replace their toothbrushes less frequently. Conclusion This study highlights significant differences in dental health practices between rural and urban children in Rwanda. Rural children were less likely to visit the dentist, consumed more sugary drinks, and used inappropriate brushing materials with less frequent toothbrush replacement. These findings underscore the need for targeted interventions to improve oral health awareness and practices especially in rural areas.